Internal polymerization of epoxy group of epoxidized natural rubber by ferric chloride filled with carbon nanotubes: Mechanical, morphological, thermal and electrical properties of rubber vulcanizates - Kriengsak Damampai; Skulrat Pichaiyut; Amit Das; Charoen Nakason (eXPRESS Polymer Letters)
In this work, the crosslinking reaction of epoxidized natural rubber (50 mol% epoxy, ENR-50) by metal ion namely ferric ion (Fe3+, FeCl3, ferric chloride) was studied. It was found that a direct interaction of the ferric ion with the epoxy group as well as internal polymerization enable the ENR to be efficiently cured. The vulcanizing ENR-FeCl3 compound was then reinforced by carbon nanotubes (CNTs). The FTIR spectra of ENR-FeCl3 compounds without and with CNTs show the absorption peak at the wavenumber 470 cm–1, which represents the –O–Fe–O– linkages from a reaction of FeCl3 and opened oxirane ring products of ENR molecules. Furthermore, the ENR-FeCl3 compounds show a typical marching curing curve with a steady increase in torque as increasing of the testing time; especially the effect is more pronounced in CNTs filled system. Furthermore, an increase in the concentration of CNTs causes increasing in torque difference and enhancement of the mechanical properties (i.e., 100% moduli and tensile strength). The SEM micrograph shows good compatibility between CNTs and the rubber matrix in the ENR-FeCl3 compounds. Also, the electrical conductivities of ENR-FeCl3/CNTs nanocomposite increases with the increase of CNTs loading. It is also observed that the degradation temperature (Td) of ENR-FeCl3/CNTs is shifted toward a higher temperature range with the increase of the CNTs loadings.